A Typical Case of Child Abuse: A Case Report - Nepal, Deepeshwara; Dhakal, Ajaya Kumar; Banstola, Dinesh; Mahaseth, Chandeshwar (Journal of Nepal Paediatric Society, 2009)
Child abuse is common but still unnoticed, undiagnosed, neglected childhood problem in Nepal. Child abuse has diverse clinical manifestation ranging from minor injury to severe head trauma to simulating severe medical problem. The true incidence of intentional head injury in children remains uncertain in Nepal. We are reporting a case of child abuse with blunt head trauma with intracranial hemorrhage presenting as a loss of consciousness simulating as a diabetic ketoacidosis (DKA) Key words: Children, child abuse, DKA DOI: 10.3126/jnps.v30i1.2462 Journal of Nepal Paediatric Society Vol.30(1) 2010 53-56